2007
DOI: 10.1111/j.1463-1318.2007.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Should indeterminate lung lesions reported on staging CT scans influence the management of patients with colorectal cancer?

Abstract: Since the introduction of spiral CT scanners, smaller lesions are being seen at the time of preoperative staging. Our study concludes that only a small proportion of indeterminate lung lesions did develop into definite metastases and those that did had node positive disease. Indeterminate lung lesions are not a reason to delay surgery for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 5 publications
5
41
0
1
Order By: Relevance
“…We agree with previous authors that finding indeterminate PNs should not prompt any modification of the treatment plan for primary colorectal cancer [14,17,30,33], but the diagnostic issue becomes particularly important in the patients concerned, because the treatment options that include surgery and chemotherapy, or some combination of them, improve for metastatic disease [34][35][36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We agree with previous authors that finding indeterminate PNs should not prompt any modification of the treatment plan for primary colorectal cancer [14,17,30,33], but the diagnostic issue becomes particularly important in the patients concerned, because the treatment options that include surgery and chemotherapy, or some combination of them, improve for metastatic disease [34][35][36].…”
Section: Discussionsupporting
confidence: 87%
“…Unfortunately, PET/CT can usually only detect nodules more than 10 mm in size [18]; percutaneous needle biopsy may be impossible or uninformative for the purposes of an accurate pathological diagnosis, depending on the size and site of nodules [31]; and video-assisted thoracoscopic biopsy is too invasive to be performed routinely [32]. Chest CT revealed growing nodules in a larger proportion of patients in our series (19/92; 20.6 %) than in other published studies, where the overall rate of ultimate diagnosis of malignancy ranged from 6.3 to 16.6 % in colorectal cancer patients found to have PNs [14,30,33]. This discrepancy may be influenced by the grounds on which pulmonary metastases are suspected, which frequently rely on inference because no final histological diagnosis is available.…”
Section: Discussionmentioning
confidence: 58%
“…5 Brent et al recently reported that only 5 of 45 indeterminate lung lesions (11%) discovered on preoperative CT scans prior to primary colorectal tumor resection ultimately were found to harbor metastatic disease. 10 Similarly, SPN are frequently detected, as high as 43% of the time as seen in our study, on preoperative CT scans of patients being considered for resection of colorectal liver metastases. It is often unclear whether these SPN represent metastatic disease, and if so, whether liver resection is the appropriate treatment.…”
Section: Discussionsupporting
confidence: 81%
“…This increased sensitivity for lung metastasis outweighs the 'nuisance' of thoracic CT detected indeterminate nodules, which are mostly benign lesions and ought not to delay management of rectal cancer [11,13,14].…”
Section: Discussionmentioning
confidence: 91%